A Multiple-Window Video Embedding Transcoder Based on H.264/AVC Standard. (4th July 2007) - Li Li, Chih-Hung Chih-Hung; Wang Wang, Chung-Neng Chung-Neng; Chiang Chiang, Tihao Tihao
Abstract : This paper proposes a low-complexity multiple-window video embedding transcoder (MW-VET) based on H.264/AVC standard for various applications that require video embedding services including picture-in-picture (PIP), multichannel mosaic, screen-split, pay-per-view, channel browsing, commercials and logo insertion, and other visual information embedding services. The MW-VET embeds multiple foreground pictures at macroblock-aligned positions. It improves the transcoding speed with three block level adaptive techniques including slice group based transcoding (SGT), reduced frame memory transcoder (RFMT), and syntax level bypassing (SLB). The SGT utilizes prediction from the slice-aligned data partitions in the original bitstreams such that the transcoder simply merges the bitstreams by parsing. When the prediction comes from the newly covered area without slice-group data partitions, the pixels at the affected macroblocks are transcoded with the RFMT based on the concept of partial reencoding to minimize the number of refined blocks. The RFMT employs motion vector remapping (MVR) and intra mode switching (IMS) to handle intercoded blocks and intracoded blocks, respectively. The pixels outside the macroblocks that are affected by newly covered reference frame are transcoded by the SLB. Experimental results show that, as compared to the cascaded pixel domain transcoder (CPDT) with the highest complexity, our MW-VET can significantly reduce the processing complexity by 25 times and retain the rate-distortion performance close to the CPDT. At certain bit rates, the MW-VET can achieve up to 1.5 dB quality improvement in peak signal-to-noise-ratio (PSNR).